ROLE OF SELF-MOTIVATION IN EMOTIONAL INTELLIGENCE OF RESEARCH SCHOLARS: AN EMPIRICAL STUDY - S. SHASHILA; RANI, S. VENNILA FATHIMA (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to explore the perception of Ph.D. research scholars in University of Madras, Chennai on dimensions and dominant groups of self motivation as a key driver for emotional intelligence. The researcher has adopted survey method to collect responses from 210 Ph.D. Research scholars pursuing their doctoral degree from University of Madras, Chennai. The statistical tools such as, percentage analysis, exploratory factor analysis, test of normality, cluster analysis and discriminant analysis has been applied to draw meaningful solutions to enhancement of emotional intelligence of Ph.D. research scholars. The result proves that Flexibility Factor (FF) Vision Factor (VF), Motivation Factor (MF) and Intrinsic Skills Factor (SIF) are the dominant dimensions of self-motivation variables. Further, Enthusiasm Seekers and Empowerment Seekers are the two cluster groups of self-motivation factors. The research scholars are recommended to maintain enthusiasm and empowerment to keep improve their emotional intelligence.